PERAN KELUARGA BESAR DALAM MEMENUHI HAK-HAK ANAK FATHERLESS MENURUT HUKUM ISLAM (Studi Kasus Desa Kwaron Kecamatan Diwek Kabupaten Jombang) - Sal Sabila Salwa; Masrokhin Masrokhin (JOURNAL SAINS STUDENT RESEARCH, 2025)
When a child becomes a victim of Fatherless such as divorce and others, there will be a break in the relationship between the child and the parent, but the role of the parent must still fulfill the child's rights such as physical and mental support, but in fact this is very much the opposite of what is in the field, precisely in Kwaron Village, Diwek District, Jombang Regency, where the child is the victim of the Fatherless, The child becomes a victim due to the impact of his parents' divorce and requires to be cared for by his grandmother, even though it should be the responsibility of his parents, this can certainly be very disturbing and have a bad impact on his future, therefore researchers are interested in researching and finding 2 interesting things to be used as problem formulations, namely the first is how the role of extended families in Kwaron Village, Diwek District, Jombang Regency fulfills the rights of Fatherless Children according to Islamic law? , and secondly, what are the factors that do not fulfill the rights of Fatherless Children in Kwaron Village, Diwek District, Jombang Regency? The approach used in this research is normative, and this type of research is qualitative. Then for the data collection methods applied include observation, interviews, and documentation, which aims to ensure that researchers actually conduct the research in question. The location of this research is located in Kwaron Village, Diwek District, Jombang Regency.From the results of the study it can be concluded that, first, some parents in Kwaron village still neglect their responsibilities in fulfilling children's rights in accordance with the provisions stipulated in Islamic Law. Second, there are several factors that cause parents in Kwaron village to neglect their obligations, including low economic levels, low education, local community habits, and lack of parental awareness of their responsibilities